‘Incidental + Intentional’ vs ‘Intentional + Incidental’ Vocabulary Learning: Which is More Effective? - Sinyashina, Ekaterina (Complutense Journal of English Studies, 2020)
This study compares the effectiveness of two combinations of new vocabulary learning techniques: ‘incidental + intentional’ and ‘intentional + incidental’. For the incidental part, the participants viewed 3 hours of captioned authentic videos, whereas for the intentional one they were asked to do a set of tasks with the target vocabulary at home. Three aspects of the target words were tested: form recognition, meaning recall and written use in a sentence. The overall scores revealed better performance of the ‘incidental + intentional’ condition in the three tests. Nevertheless, a variety of scores in the sample for the three aspects of word knowledge and the lack of statistical evidence did not allow us to conclude with certainty which combination is more or less effective for new vocabulary learning.